Kvantifiering av föroreningstransport till recipient : Luleå flygplats - Wahlskog, Cecilia (2011)
At Luleå airport urea is used as deicing agent as it dissolves ice coatings by lowering the freezing point of water. Urea occur natural in water courses and soils as the result of excretion and degradation of nucleic acids and proteins. The contents are usually low in the natural environment. Large amount of urea were added because of the deicing, 145 tons in the season 2009/2010. Urea consists of 46 % nitrogen which occurs as ammonium whose emissions can lead to eutrophication and can be toxic for organisms in high contents. In a study from SGU in 1996 it was showed that a maximum of 10 % of the urea nitrogen from Luleå airport leaks in to Bottenviken every year, which suggests that the main part of the urea nitrogen infiltrate into the ground, is taken up by plants or leaves as nitrogen gas through denitrification. Luleå airport has two infiltrations ponds, the north and the south, where all of the airports stormwater sewers link together. Approximately 75 % of the stormwater that drains from Luleå airport runs to the south infiltration pond where an oil trap is placed as a first cleaning step. In 2008 an overflow trench was built between the south infiltration pond and the recipient Lulkroksviken to prevent the flooding that regularly took place, causing forest damages. Only the south infiltration pond with its associated overflow trench was included in this thesis. At the same time as the overflow trench was built a sharp edged weir with a pressure sensor were installed in a well placed at the outlet of the trench to measure the flow that passes. In 2010 a control program to assess the direct emissions from the airport area to the recipient through stormwater started, including regular sampling of the overflow water and analysis of the total nitrogen, total phosphorus, suspended solids, conductivity and pH. Also included in the control program were to sample some elements, PFOS and oil compounds at some occasions to get an entire comprehension of the water quality and possible contaminant transport. The ...